Answer:
Step-by-step explanation:
Use FOIL method
1) (x +4 )(3x +2) = x*3x + x*2 + 4*3x + 4*2
= 3x² + 2x + 12x + 8
= 3x² + 14x + 8
4) (4x - 1) (2x + 7) = 4x*2x + 4x*7 + (-1)*2x + (-1) * 7
= 8x² + 28x - 2x - 7
= 8x² + 26x - 7
Answer: 13
Step-by-step explanation:
If you remember the quadratic equation formula;
![x=\frac{-b\frac{+}{}\sqrt{b^2-4ac} }{2a}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-b%5Cfrac%7B%2B%7D%7B%7D%5Csqrt%7Bb%5E2-4ac%7D%20%20%7D%7B2a%7D)
You can easily extract what is under the root to find the discriminant.
![b^2-4ac=?\\](https://tex.z-dn.net/?f=b%5E2-4ac%3D%3F%5C%5C)
a = 3
b = 7
c = 3
![(7)^2-4(3)(3)\\49-36=13](https://tex.z-dn.net/?f=%287%29%5E2-4%283%29%283%29%5C%5C49-36%3D13)
Answer:
p=5i
Step-by-step explanation:
(p^(4)=-25p^(2))/p^(2)
p^(2)=-25
Square root both sides
p=5i
i is the square root of -1, so 5i is five times that much.
The square root of a negative number in not real. That is why it is i, and not a number.
Answer: Number one would be 3x+2y+-14 and x+y=-4, second one is x=-3, y=7
Step-by-step explanation:
The first one is solved by inputting the x and y in each one and finding which one comes out true, the second on is solved by substitution. to find x you would subtract x in the first equation and make it y=4-x then input that equation in the y in the second equation.
100% of the original number